Mobile health technology combats COVID-19 in China. Issue 1 (January 2021) - Wu, Jieyu; Xie, Xiaowei; Yang, Le; Xu, Xingyan; Cai, Yingying; Wang, Tinggui; Xie, Xiaoxu
Highlights: Internet hospitals alleviate the unavailability, inaccessibility, and inequity of health services during the outbreak. Fact-check and information-release platforms reduce the spread of misinformation. Health QR codes facilitate restoring the order of production and life. Mobile health technologies support China fight against COVID-19. Abstract: China empowers mobile health technologies to fight against COVID-19 pandemic. The success of mobile health here may be a useful reference for other parts of the world. We explore China's application of mobile health technologies to replenishing traditional public-health and social approaches for mitigating and suppressing COVID-19, and found that Internet hospitals alleviate the unavailability, inaccessibility, and inequity of health services during the outbreak; the fact-check and information-release platforms reduce the spread of misinformation; and the infection risk scoring systems facilitate restoring the order of production and life. Graphical abstract: Image, graphical abstract